A survey on the impact of the coronavirus disease 2019 pandemic in Portuguese physical and rehabilitation medicine departments - Branco, Catarina A; Branco, João P; Branquinho, Lurdes R; Pinheiro, João (Archives of Community Medicine and Public Health, 2021)
Introduction: The pandemic Coronavirus Disease 2019 (COVID-19) strongly affected the organization and functioning of Physical and Rehabilitation Medicine (PRM) departments in Europe, posing specific challenges in the management of diseases and their consequences. We aim to evaluate the changes suffered by Portuguese PRM departments in the scope of assistance, organization, training and research. Methods: A self-administered, cross-sectional online questionnaire was sent to 41 Portuguese PRM departments, regarding the assistance provided to patients with COVID-19, organizational changes and difficulties experienced on team management, training and research. Results: The survey had a response rate of 82.9%. The majority of the PRM departments assisted patients with COVID-19, mainly in the context of inpatient general ward care and intensive care units. Changes in the assistance activity and accessibility were reported by almost all PRM departments, mainly affecting the outpatient consultation. There was a reduction on the number of healthcare professionals reported, especially by transfer to other areas, and almost all used remote procedures, especially for patient reassessment, counseling, and monitoring. The majority of PRM departments highlighted the pandemic’s impact on the training availability, as well as in the applied research and publications. Conclusions: The pandemic triggered a complete overhaul of rehabilitation departments with significant changes in assistance activity, changing routines and programmed procedures, with a strong negative impact on scientific research and training. Outpatient consultations was the most affected area, while support for hospitalization and internal consultations remained mostly operational. The use of remote procedures was high, particularly in follow-up and counseling.